The Role of Anti-Violence Education in Creating a Safe Learning Environment: A Study at Pondok Pesantren Modern Selamat Kendal - Anwar, Ahnun Daim Khoiri; Putri, Yunita Ardila; Khanifah, Milkhatun; Khasanah, Nikmatul; Kamil, Tasallia Nima; Zafi, Ashif Az (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to explore the role of anti-violence education in creating a safe learning environment at Pondok Pesantren Modern Selamat Kendal. Islamic boarding schools are often environments where physical and psychological violence can occur due to strict disciplinary practices and rigid educational systems. However, the implementation of anti-violence education is expected to foster a more conducive atmosphere for the psychological and academic development of students. This research employs a qualitative case study approach, with data collected through in-depth interviews, observations, and document analysis. The findings indicate that the implementation of anti-violence education in this pesantren has helped reduce incidents of violence, strengthen interpersonal relationships between teachers and students, and enhance the sense of safety and comfort in the learning environment. The application of anti-violence principles involves reinforcing religious values, ethical educational practices, and active engagement from the pesantren in providing guidance and counseling to students. The study also identifies challenges, such as resistance from some educators who still adhere to traditional methods. These findings contribute significantly to the development of more humanistic educational policies in Islamic boarding schools.